Interview with the Engineer of a Polish Fishing Vessel Information on Conditions in the Fishing Industry, Short-age of Repair Materials and Forthcoming Recruitment of Surplus WOP for Fishing Fleet - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Item based on interviews conducted with defectors and immigrants in Western refugee camps and immigration offices, or Western travelers returning from stays in East European communist countries, supplemented with information collected through Radio Free Europe (RFE) correspondence with anonymous sources from behind the Iron Curtain. This item was transmitted from the Hamburg field office. This field report was assigned the following topical and geographical subject headings by the RFE/RL: Poland; Agriculture -- Manpower; Labor -- Wages and Hours; Police and Security -- Political Police; Religion -- Roman Catholic Church (2806); Industry -- Fishing (1714); Religion -- Persecution; Industry -- Difficulties In Production; Labor -- Voluntary Contribut